Fiber-Enhanced Raman Gas Spectroscopy for the Study of Microbial Methanogenesis - Knebl, Andreas; Domes, Robert; Wolf, Sebastian; Domes, Christian; Popp, Juergen; Frosch, Torsten (Analytical Chemistry, 2020)
Microbial methanogenesis is a key biogeochemical process in the carbon cycle that is responsible for 70% of global emissions of the potent greenhouse gas methane (CH4). Further knowledge about microbial methanogenesis is crucial to mitigate emissions, increase climate model accuracy, or advance methanogenic biogas production. The current understanding of the substrate use of methanogenic microbes is limited, especially regarding the methylotrophic pathway. Here, we present fiber-enhanced Raman spectroscopy (FERS) of headspace gases as an alternate tool to study methanogenesis and substrate use in particular. The optical technique is nondestructive and sensitive to CH4, hydrogen (H2), and carbon dioxide with a large dynamic range from trace levels (demonstrated LoDs: CH4, 3 ppm; H2, 49 ppm) to pure gases. In addition, the portable FERS system can provide quantitative information about methanol concentration in the liquid phase of microbial cultures through headspace gas sampling (LoD 25 ppm). We demonstrate how FERS gas sensing could enable us to track substrate and product levels of microbial methanogenesis with just one instrument. The versatility of Raman gas spectroscopy could moreover help us to elucidate links between nitrogen and carbon cycle in microbial communities in the near future.
CRIS-Team Scopus Importer:2023-04-20